Isolated oropharyngeal abscess with hypopharyngeal extension recurring 12 years after initial surgical management: A case report and review of the literature. (April 2022) - Khoury, Michel; Dong, Selina Xiangxu; Alsaffar, Hussain; Johnson-Obaseki, Stephanie; Caulley, Lisa
Pharyngeal abscesses require urgent management as they have the propensity to cause severe and life-threatening complications. The introduction of antibiotics has led to a dramatic decline in the incidence of these infections. Regardless, abscess formation continues to be observed in the peritonsillar, parapharyngeal, and retropharyngeal spaces. Oropharyngeal and hypopharyngeal abscesses that cause airway obstruction are scarcely reported and tend to be secondary to other processes. Herein, we describe the case of an 83-year-old man presenting with an idiopathic, obstructive, oropharyngeal wall abscess, extending from the infratonsillar region to the hypopharynx, which recurred after initial surgical management 12 years prior for the same process. He required reintervention during both episodes for rapid reaccumulation. A detailed electronic literature search of PubMed and MedLine was performed for studies reporting on recurrent pharyngeal abscesses and their management. Results were limited to articles published in English from inception to August 2021. The timely management of pharyngeal infections acutely obstructing the airway is crucial. Physicians should adopt close and frequent monitoring and have a low threshold for reimaging should symptoms worsen or fail to improve after the initial surgical intervention.